2022
DOI: 10.37201/req/022.2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Staphylococcus aureus bacteremia in COVID-19 patients

Abstract: Introduction. The disease caused by SARS-CoV-2 (COVID-19) has been a challenge for healthcare professionals since its appearance. Staphylococcus aureus has been described as one of the main pathogens causing bacterial infections in viral pandemics. However, co- infection with S. aureus causing bacteremia in patients with COVID-19 has yet to be well studied. Methods. We performed a e study of S. aureus bacteremia (SAB) at Hospital Miguel Servet (Zaragoza) from March 2020 to February 2021. The clinical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Persistent or recurrent staphylococcal bacteriaemia related to SD in the COVID-19 pandemic has been reported in other cases of young healthy patients and unapparent infectious foci, speculated to be accounted to the immune disfunction, with secondary (reactive) hemophagocytic lymphohistiocytosis and to the diffuse vascular damages [ 32 , 33 , 34 , 35 ]. The first line of anti-staphylococcal antibiotics aimed highly antibiotic resistant MRSA but resulted in incompletely recovery after six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent or recurrent staphylococcal bacteriaemia related to SD in the COVID-19 pandemic has been reported in other cases of young healthy patients and unapparent infectious foci, speculated to be accounted to the immune disfunction, with secondary (reactive) hemophagocytic lymphohistiocytosis and to the diffuse vascular damages [ 32 , 33 , 34 , 35 ]. The first line of anti-staphylococcal antibiotics aimed highly antibiotic resistant MRSA but resulted in incompletely recovery after six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent COVID-19 Pandemic, it was reported that when the patients infected with SARS-CoV-2 were co-infected with S. aureus, especially when exposed to mechanical ventilation and/or receiving steroid therapy, the risk of mortality increased, and even the 30-day mortality was 67% 26,27 . Local epidemiological studies are needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies are currently being conducted in patients with COVID-19 who also suffer from a bacterial infection, specifically bacteraemia. An increasing incidence of coinfections in patients admitted to the ICU and an increased rate of infection with nosocomial MDR bacteria have been observed, creating the need for special care in the treatment of patients with COVID-19 [ 123 ].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…The most frequent source of bacteraemia caused by S. aureus was respiratory (26.9%) followed by cutaneous (15.5%). Concluding that bacteraemia caused by this pathogen negatively influences the outcome of patients with COVID-19, suggesting that further studies are needed to obtain robust data on the impact of bacteraemias caused by S. aureus in patients infected with SARS-CoV-2 [ 123 ].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%